IMPLEMENTASI KEBIJAKAN INKLUSIF PONDOK SOSIAL KALIJUDAN SURABAYA - Rio Febriannur Rachman (Khazanah Intelektual, 2020)
This article discusses the inclusive policies taken by the Surabaya City Government in handling Children with Special Needs (ABK) and being displaced in the Kalijudan Social Cottage (Pondok Sosial Kalijudan). The question to be answered through this paper is how to implement this policy and its relation to sustainable development goals. To answer these questions, an in-depth study of the data from the Surabaya Social Service, mass media reports, and observation were conducted directly at the Kalijudan Social Cottage. As the result, this policy has formed a system that opens opportunities for ABK and is neglected to achieve. In addition, this policy is in line with a number of points of sustainable development goals launched by the United Nations.